GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - Kimsen Kimsen (Univesitas Muhammadiyah Tangerang, 2022)
This study aims to determine the effect of Good Corporate Governance on tax management. Good Corporate Governance in this study uses the proxy of the board of commissioners, independent commissioners and the audit committee. The board of commissioners is measured by looking at the total number of members who are members of the board of commissioners, independent commissioners are measured by the number of independent commissioners over the total board of commissioners of the company and the audit committee is measured by the number of audit committees in the company. Tax management in this study is measured by effective tax rates (ETR). The population in this study are food and beverage companies listed on the Indonesia Stock Exchange during the 2017-2020 period. The total samples tested were 9 companies selected by purposive sampling technique so that the analyzed data amounted to 54 companies. The data analysis technique used panel data regression with the help of the Eviews 9.0 program. The results of this study indicate that (1) the board of commissioners has a significant positive effect on tax management, (2) Independent Commissioners have no effect on tax management, (3) The Audit Committee has a significant negative effect on tax management, Keywords: Tax Management, Effective Tax Rate, Good Corporate Governance